Population attributable fractions of clinical and social risk factors for suicide in Bangladesh: Finding from a case–control psychological autopsy study. Issue 12 (10th November 2021) - Arafat, S. M. Yasir; Khan, Md. Abdullah Saeed; Knipe, Duleeka; Khan, Murad M.
Abstract: Background: Our knowledge of suicide in low‐income countries is limited. Understanding the importance of factors that contribute to suicide risk will allow for the appropriate allocation of limited resources. In order to prioritize suicide prevention activities in Bangladesh, we estimate the fractions of suicides attributable to key risk factors. Methods: Using data from matched cases (100) and controls (100) as part of a psychological autopsy study in Dhaka, we estimate the population attributable fraction for key clinical (psychiatric disorders and physical disability), and social (life events, psychical and/or sexual abuse, unemployment, and social isolation) risk factors for suicide in Bangladesh. Results: Assuming a causal relationship, life events were responsible for the largest proportion of suicide deaths (85.9%; confidence interval [CI], 79.6–90.2), followed by mental disorder (49.5%; CI, 45.3–53.4). The population attributable fraction for the risk factors was 42.9% (CI, 40.6–45) for depression, 11% (CI, 8.9–13) for sexual abuse, and 34.9% (CI, 10.1–52.9) for social isolation. Conclusions: The study determined the population attributable fraction of risk factors for suicide in Bangladesh. Prevention strategies should be prioritized on the management of the aftermaths of adverse life events, treatment of psychiatric disorders, sexual abuse, and social isolation in the country. Abstract : This is the first study determining the population attributable fraction of risk factors for suicide in Bangladesh. Adverse life events were responsible for the largest proportion of suicide, followed by mental disorders. Prevention strategies should focus on the management of key social and clinical risk factors.